Species-rich but defaunated: the case of medium and large-bodied mammals in a sustainable use protected area in the Amazon - ROSA, Dian Carlos Pinheiro; BROCARDO, Carlos Rodrigo; ROSA, Clarissa; CASTRO, Arlison Bezerra; NORRIS, Darren; FADINI, Rodrigo (Acta amazonica, 2021)
ABSTRACT Neotropical medium and large-bodied mammals are key elements in forest ecosystems, and protected areas are essential for their conservation. In Brazil, sustainable use protected areas (SU-PAs) allow both the conservation of biodiversity and the sustainable use of natural resources, especially in the Amazon region. However, SU-PAs usually suffer both internal and external pressures, and may be subject to variable degrees of defaunation. We sampled mammals using camera traps in two areas with different forest management and human occupation history in the Tapajós National Forest (TNF), in the western Amazon. Overall, we recorded a rich assemblage of medium and large-sized mammals, though both areas differed in species composition. The area with older and more intense human occupation and forest exploitation had more independent records of generalist species, while large species such as Tapirus terrestris and Panthera onca were recorded exclusively in the area with lower human occupation and no forest management. A comparison of our results with similar studies in other Amazonian sites suggests a reduction in the population size of large-bodied mammals, such as Tapirus terrestris and Tayassu pecari, likely in response to increased human activities. Local differences in human occupation within and between protected areas are common in the Amazon, demanding area-specific actions from public authorities to minimize impacts on wildlife caused by human activities. Specifically in TNF, we recommend long-term monitoring of the responses of mammals to human activities, to better subsidize conservation and management actions. RESUMO Mamíferos neotropicais de médio e grande porte são elementos chave em ecossistemas florestais, e unidades de conservação são essenciais para sua conservação. No Brasil, as unidades de conservação de uso sustentável (UC-US) permitem tanto a conservação da biodiversidade quanto a exploração sustentável dos recursos naturais, especialmente na Amazônia. Porém, as UC-US geralmente são afetadas por pressões internas e externas, e podem apresentar diferentes graus de defaunação. Amostramos mamíferos de médio e grande porte usando armadilhas fotográficas em duas áreas com distintos históricos de manejo e ocupação humana na Floresta Nacional do Tapajós (FNT), na Amazônia ocidental. Em geral, registramos uma rica assembleia de espécies de mamíferos de médio e grande porte, mas as duas áreas diferiram na composição de espécies. A área com ocupação humana mais intensa e antiga e exploração florestal apresentou mais registros independentes de espécies generalistas, enquanto espécies maiores, como Tapirus terrestris e Panthera onca, foram registradas exclusivamente na área com menor ocupação humana e sem manejo florestal. A comparação de nossos resultados com estudos similares em outros locais na Amazônia sugere uma redução no tamanho populacional de mamíferos de grande porte, como Tapirus terrestris e Tayassu pecari, provavelmente em resposta ao aumento das atividades humanas. Diferenças locais na ocupação humana dentro de e entre unidades de conservação são comuns na Amazônia, demandando ações específicas do poder público para minimizar impactos de atividades humanas sobre a fauna silvestre. Especificamente na FNT, recomendamos o monitoramento de longa duração das respostas de mamíferos às atividades humanas, para melhor embasar ações de conservação e manejo.